The effects of different types of dance interventions on the autonomic nervous system of college students with depressed mood - Zhao, Ruixue; Li, Jiayi; Wang, Jiameng (Frontiers in Psychology, 2025)
PurposeThis study aims to compare the regulatory effects of different dance styles (such as modern dance, Chinese classical dance, jazz dance, and ballet) on depressive mood, with a particular focus on their impact on the autonomic nervous system function (e.g., HRV indicators). The goal is to identify the most therapeutically promising form of dance intervention and provide more effective supplementary approaches for individuals experiencing depressive mood.MethodsThis study involved screening 1,500 university students for Depressive mood out of a total of 10,784 students at the university (Anonymize) (p > 0.05). From the 1,500 individuals identified with depressive mood, 150 were randomly selected for the intervention. These participants were then randomly assigned to five groups: group A (classical dance), group B (ballet), group C (jazz dance), group D (modern dance), and group E (control group). The intervention consisted of dance practice four times weekly for 20 min per session over 12 weeks. Baseline demographic data, including age, gender, height, weight, and Body Mass Index (BMI), were collected, and participants completed the Self-Rating Depression Scale (SDS) test before the intervention began. Data organization was performed using Excel, and SPSS 22.0 was used for analysis.ResultsBefore the intervention, Heart Rate Variability (HRV) indicators showed no significant differences between groups (p > 0.05). However, during the recovery period, heart rate (HR) was notably higher after modern dance than after the other dance forms. The HRV index was significantly higher than those in the ballet and classical dance groups (p < 0.05). The modern dance group also showed a significant reduction in the SDS index compared to the classical, ballet, and jazz dance groups (p < 0.05).ConclusionModern dance may, therefore, be more effective in promoting recovery for individuals with depressive mood than Chinese classical, ballet, or jazz dance.